Hiring ex-offenders: an application of theory of planned behaviour / Fatin Nadirah Khasni, JS Keshminder and SC Chuah - Khasni, Fatin Nadirah; Keshminder, JS; Chuah, SC (Faculty of Business and Management, 2021)
Ex-offenders released from incarceration experience difficulties securing accommodation, finding stable work, and connecting with families. Although ex-offenders have numerous noteworthy problems, ensuring gainful employment has always been inferred as the most difficult challenge. Many offenders who attempt to acclimate themselves to the society demonstrated gaps in their work history, limited skill sets, and incomplete education. This study deploys the Theory of Planned Behaviour and literature reviews to conceptualise the factors that impact employers' intention to hire ex-offenders. Specifically paying attention to employers who are hiring and have hired ex-offenders to work in their companies or organisations, the study proposes a hiring intention research model.